Using Event-Related Brain Potentials to Assess Perceptibility: The Case of French Speakers and English [h] - Mah, Jennifer; Goad, Heather; Steinhauer, Karsten (Frontiers in Psychology, 2016)
French speaking learners of English encounter persistent difficulty acquiring English [h], thus confusing words like eat and heat in both production and perception. We assess the hypothesis that the acoustic properties of [h] may render detection of this segment in the speech stream insufficiently reliable for second language acquisition. We use the mismatch negativity (MMN) in event-related potentials to investigate [h] perception in French speaking learners of English and native English controls, comparing both linguistic and non-linguistic conditions in an unattended oddball paradigm. Unlike native speakers, French learners of English elicit an MMN response only in the non-linguistic condition. Our results provide neurobiological evidence against the hypothesis that French speakers’ difficulties with [h] are acoustically based. They instead suggest that the problem is in constructing an appropriate phonological representation for [h] in the interlanguage grammar.